Sustainable Closed-Loop Supply Chains in Beer Industry - Pokorný, Petr; Fiala, Petr, 1949-; Brezina, Ivan; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
Supply chains in the beverage industry are going through a turbulent period when they are exposed to the growing trend of environmental behaviour from consumers, the increasing influence of retail chains, external regulation from national and multinational entities and the related emphasis on the cost structure of individual members of the chain. All these influences have one common denominator, which is the sustainable profitability of each player and the chain as a whole within the framework of its competitiveness. In this paper, we focus on all the above-mentioned influences and analyze the impacts of the decisions of the individual members of these chains, which are classified as Closed-Loop Supply Chain or CLSC, because a certain type of consumer-packaging is put back into circulation. This characteristic introduces another important parameter in the decision-making of the individual members, whereby a higher level of closure is seen as a lower proportion of non-returnable packaging used throughout the chain. We analyse the effects of the above factors on the decision-making of individual members of supply chains on a theoretical basis and also using real data, specifically from the beer industry. The modelling apparatus is mainly Game Theory allowing to analyse the reasons and consequences of decisions and to perform sensitivity analyses. The use of real data from the beer industry environment and the equilibrium solutions derived from it proves to be crucial in comparing real decisions and the performance of chains in practice with what profit-measured performance could be achieved with coordination and managed cooperation within a given chain, which is often hindered by the dominant role of retail. Specifically, in this paper we provide evidence on the profitability of ecologically transformed CLSCs and derive the conditions under which it is sustainable and how it relates to consumer behavior.
We derive a new type of coordination contract and provide evidence on the reciprocal equality of the contractionary conditions of two different very commonly used coordination contracts in beer CLSCs, namely the wholesale discount and the reverse sales bonus. In the section on the so-called Deposit-Refund System (DRS), we analyze the implications of the planned introduction of the deposit system in the Czech Republic and derive conditions for its efficiency and a method for estimating the optimal deposit amount under existing market conditions. One of the outcomes is the key role of the regulating entity, the non-profit organization, and its impact on the importance of the recycler as one of the actors. The last study shows the irrational behaviour of CLSC members, where the dominant retailer could increase its profit by enforcing a coordination contract, but in practice does not do so. This paper derives evidence that the trade-off so-called Stackelberg solution can be transformed into a Nash solution from which all members can profit, even though this does not happen in practice.
Vedoucí práce: Petr Fiala
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: ekonometrie a operační výzkum [obor disert. práce]; disertace; dissertations